THE CORELLATION BETWEEN LEADERSHIP STYLE AND NURSES JOB SATISFACTION IN WONOSARI REGIONAL HOSPITAL OF YOGYAKARTA - Indriyani, Yenni Agustina; Istichomah, Istichomah; Monika, Rika (Jurnal Kesehatan Samodra Ilmu (JKSI), 2020)
ABSTRACT Background: Leadership style is a process undertaken by the manager to direct and influence his subordinates so that subordinates are willing to use all of the abilities optimally. Leadership style consists of autocratic, democratic, and free action. Job satisfaction is a nurses emotional response to various aspects of work while on duty in the medical ward, consisting of satisfied and dissatisfied. Job satisfaction is needed for nurses to improve health services, by changing the leadership style received by their subordinates. Then their subordinates can carry out their duty and responsibilities even better, so the hospital goals will be maximally achieved. Objective: This research determine the relationship between nursing managers leadership style and nurses job satisfaction in Wonosari Regional General Hospital of Yogyakarta. Method: The method used in this research is an analytical survey using quantitative research methods by a cross sectional approach. The sampling technique used is random sampling with 85 nurses sample, the data collection method used is by filling out a questionnaire. Data analysis was carried out by univariate and bivariate analysis through Chi-Square test. Result: The results of the Chi-Square test were -0,351 with a significant value of 0,001 <0,05). These results indcate that there is a realationship between nursing manager leadership style and nurses job satisfaction in Wonosari Regional General Hospital of Yogyakarta. Leadership style that is often applied in Wonosari Regional General Hospital of Yogyakarta is a democratic leader ship style and the job satisfaction of nurses is in the very satisfied category. Conclusion: There is a correlation between nursing manager leadership style and nurses job satisfaction in Wonosari Regional General Hospital of Yogyakarta.